Effects of high fluoride drinking water on the cerebral function of mice - Sun, Z; Liu, F; Wu, L; Lu, Y; Yu, D (Fluoride, 2008)
Objective: To study the effects after six months of exposure of mice to increasing concentrations of fluoride in drinking water (tap water, 10, 50, and 100 mg F/L) on their cerebral functions. Methods: Learning and memory abilities of high-fluoride exposed and control groups of mice were measured by a behavior-toxicological test (Shuttle-box Test), and the cholinesterase (ChE) activity in brain tissue homogenates of the mice was determined. Results: Learning and memory abilities of the fluoride-exposed groups were significantly lower than those of the control group, and the brain ChE activities of the fluoride-exposed groups were significantly higher. Conclusions: Elevated fluoride concentration in drinking water can decrease the cerebral functions of mice. Fluoride is a neurotoxicant.